(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the article the history of the appearance of Azerbaijan-European literary relations is investigated. The author reveals all existing meanings of the term «the literary connections» and studies the literary connections till the 20th century particularly. According to the author’s thought the connection in the literary level can be from one-sided or mutual interest, and out of necessity. The same process occurs in the life of peoples and cultures, including in the literary process of Azerbaijan. Investigating the theory of literary relations in the article these relations are classified on communication generated interest in the literature of the other nations and relations, generated by the need in the literature of other nations. The author of the article concludes that existed at the same or at different times among the individual national literatures or their individual representatives, in general, can occur through the contact of the contingent similarities history of the literary process and the similarities of being the cause of the sociohistorical process